The Use of Quizizz Aplication for Al-Islam Lesson to Enhance Learning Efectiveness: Penggunaan Aplikasi Quizizz pada Pembelajaran Al-Islam untuk Meningkatkan Efektivitas Pembelajaran - Afifa, Elverda Zahra; Arifin, Moch. Bahak Udin By (Pedagogia : Jurnal Pendidikan, 2026)
This study aims to examine the effectiveness of using the Quizizz application in Al-Islam learning for 11th grade students at SMA Muhammadiyah 4 Porong. This study uses a quantitative approach with pre-test and post test design with a single group sample consisting of 14 people. The results of the study indicate that the application of Quizizz in Al-Islam learning can improve student learning outcomes. This proves that Quizizz is able to create a more interactive and enjoyable learning atmosphere and can increase student motivation to learn. Therefore, the use of Quizizz application can be an effective alternative learning medium in supporting the implementation of Al-Islam learning at the high school, especially in the context of the class studied. Highlights: Statistical testing demonstrated significant score differences between initial and final assessments (p = 0.002). Most participants achieved scores within the highest interval range after treatment. Game-based digital instruction fostered active classroom participation and measurable academic progress. Keywords: Quizizz App, Learning Effectiveness, Al-Islam